A Case Report: Red Skin Syndrome- as the Rebound Effect of Using a Long Term Potent Topical Corticosteroid - Octaviani, Cristine D. (Indonesian Journal of Clinical Pharmacy, 2014)
31 years old male suffered from a rare skin disorder, diagnosed of red skin syndrome. Seven years ago, symptoms was begun with a light itching on skin area of body as well as face, and visited a general  practitioner,  diagnosed  of  light  allergic  rhinitis.  He  was  prescribed  oral  corticosteroid, methyl prednisolone 4 mg b.i.d and very potent topical corticosteroid, clobetasol. The symptoms was significantly disappeared and being rebound after stopping the prescription. To maintain this rebound effect, for seven years in on-off unhealed conditions, he used topical cream corticosteroid, clobetasol, that fully masked this worst rebound condition. When application of the topical cream was stopped, rebound effect relapsed and even red skin syndrome became worse than before. After20 months of being fully stopped from corticosteroid, the symptoms finally slowly reduced. He almost fully recovered and had a normal life until now December 2013. By this case, we can learn that this red skin syndrome, resulted from side effect of corticosteroid, will be stopped by fully stopping administering orally or topically, and this will take quite long time for skin to recover.Key words: Corticosteroid, rebound, red skin syndrome Studi Kasus: Red Skin Syndrome sebagai Efek Penggunaan Kortikosteroid Topikal dalam Waktu LamaSeorang lelaki berumur 31 tahun menderita gangguan kulit yang didiagnosis sebagai red skin syndrome. Sekitar tujuh tahun yang lalu, gejalanya diawali dengan gatal ringan pada daerah kulit tubuh dan wajah, serta sempat datang berobat ke dokter umum dan didiagnosis sebagai rinitis alergi ringan. Pasien diresepkan kortikosteroid oral methyl prednisolone, 4 mg b.i.d dan krim clobetasol. Dengan pemberian ini dalam waktu tiga hari gejalanya langsung hilang namun kembali muncul ketika pemakaian obat dihentikan, tanpa tapering off. Dalam menjaga keadaan kulitnya, selama kurang lebih tujuh tahun dengan keadaan hilang-kambuh, pasien menggunakan pengganti kortikosteroid oral, yaitu krim topikal kortikosteroid clobetasol yang kemudian dapat menutupi kondisi on-off rebound tersebut. Ketika penggunaan krim topikalnya dihentikan, efek rebound kembali muncul bahkan dengan kondisi yang lebih buruk. Setelah berhenti total 20 bulan dari penggunaan terakhirnya, perlahan gejalanya mereda. Keadaan pasien membaik hingga bulan Desember 2013. Red skin syndrome sebagai efek samping dari pemberian topikal kortikosteroid baik oral maupun topikal pada kasus ini dapat dihentikan total dengan cara menghentikan seluruh pemberian obat dan menunggu waktu cukup lama hingga kulit kembali pulih. Kata kunci: Kortikosteroid, rebound effect, red skin syndrome